2020
DOI: 10.3390/rs12040638
|View full text |Cite
|
Sign up to set email alerts
|

Historical Aerial Surveys Map Long-Term Changes of Forest Cover and Structure in the Central Congo Basin

Abstract: Given the impact of tropical forest disturbances on atmospheric carbon emissions, biodiversity, and ecosystem productivity, accurate long-term reporting of Land-Use and Land-Cover (LULC) change in the pre-satellite era (<1972) is an imperative. Here, we used a combination of historical (1958) aerial photography and contemporary remote sensing data to map long-term changes in the extent and structure of the tropical forest surrounding Yangambi (DR Congo) in the central Congo Basin. Our study leveraged struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…These findings match those found by Yila and Resurreccion (2014) in Nigeria and Tesfahun and Chawla (2019) in Ethiopia. However, slash-and-burn agriculture as a cause of climate change has been cited at local (Hufkens et al , 2020), national (MECNT, 2012; Molinario et al , 2015) and international levels (Pan et al , 2011; Arneth et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings match those found by Yila and Resurreccion (2014) in Nigeria and Tesfahun and Chawla (2019) in Ethiopia. However, slash-and-burn agriculture as a cause of climate change has been cited at local (Hufkens et al , 2020), national (MECNT, 2012; Molinario et al , 2015) and international levels (Pan et al , 2011; Arneth et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite the fact that agriculture is considered as the most vulnerable sector to climate change at both local and national levels (MECNT and UNDP, 2009; Ulimwengu and Kibonge, 2016); several studies have shown that it is a major source of greenhouse gas (GHG) emissions (Pan et al , 2011; Arneth et al , 2019), through the process of deforestation (Potapov et al , 2012; Hufkens et al , 2020), thus contributing to climate change (Kipalu and Mukungu, 2012; AMCEN, 2014). Slash-and-burn agriculture is the main direct cause of deforestation in DRC (MECNT, 2012; Molinario et al , 2015), particularly in the Yangambi landscape (Hufkens et al , 2020). The search for fertile land pushes the population to clear increasingly more forest areas to meet their ever-increasing needs and to cope with greater demographic pressure (Alongo et al , 2013; Kyale et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…well as the trafficking of ivory and skins (van Vliet al, 2018). Annual deforestation rates on primary forests subsequently increased after about 2010 (Hufkens et al, 2020). These impacts mostly reflect a growing human population as the post-conflict period provided greater stability for people looking to invest in agriculture.…”
Section: Figurementioning
confidence: 99%
“…At the same time, deforestation and the unbalanced functioning of forest ecosystems have wider effects and environmental consequences including land degradation, desertification, the loss of wildlife habitat and soil erosion [34]. Analysis of deforestation is possible by comparing forest areas on older maps with those detected on the remote sensing data [35][36][37] or landscape dynamics evaluated by time series of images [38]. Other approaches include continuous metrics to measure the degree of forest degradation [39] While the techniques of the remote sensing data acquisition and image processing by Geographic Information System (GIS) have demonstrated advances over recent decades [40,41], the algorithms of geospatial data modelling are not as straightforward regarding handling the data automatically.…”
Section: Introductionmentioning
confidence: 99%